SEEN, BUT IGNORED: A CRITICAL REVIEW ON MENSTRUAL HYGIENE PRACTICES IN INDIA - Shreyas Bharath, (EPRA International Journal of Research and Development (IJRD), 2023)
Adolescent girls make up 8% of the total world population (estimated to be 0.6 billion) (World Bank, 2023); and improper menstrual hygiene can have long-lasting impacts on their health which may lead to period poverty, and wide-spread economy-wide spill-over effects (Khan, 2023). The continuing efforts of the World Bank to improve menstrual health management (MHM) is evident in the proportion of its ongoing projects involving menstrual health promotion (43 out of 178 projects as of Feb, 2022) (World Bank, 2023). Despite gaining attention in recent years, menstrual hygiene is a less familiar topic among the “355 million menstruating women in India” (World Bank, 2023). In the current article, the author will first, review the current state of menstrual health management in India and present reasons for the same. Second, it sheds light on the several policy efforts undertaken by the Indian government, NGOs, and citizens. Lastly, it presents suggestions on better MHM by referring to successful event studies and pilot projects.